Analisis Kemometrika Kandungan Fitokimia dan Uji Anti Acne Ekstrak Etanol 70% dan Etil Asetat Daun Alpukat : (Persea Americana Mill) - Pramesti Anggun Asyifa; Endang Setyowati; Fahrudin Arif (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Human skin requires care to prevent and treat acne caused by Propinobacterium acnes bacteria. Researchers are exploring the use of avocado leaves as a natural therapy to treat acne. Avocado leaves contain antibacterial and anti-inflammatory compounds such as flavonoids, saponins, and alkaloids. This study aims to measure the total flavonoid and phenolic content in extracts obtained with 70% ethanol and avocado ethyl acetate and analyze their anti-acne activity. Total flavonoids were determined using a reagent consisting of 10% AlCl3 and 5% acetic acid. Total phenolic determination was carried out using the Folin-Ciocalteu reagent with gallic acid as a reference standard. Measurement of phytochemical levels used the UV-Vis spectrophotometry method. Antibacterial testing was carried out using Staphylococcus aureus bacteria with concentrations of 12%, 14%, and 16%. The positive control used clindamycin. The negative control used 10% DMSO. The disc diffusion method was used to observe the inhibition zone in this study. The results of this study will be processed using chemometrics to analyze complex chemical data. The data results showed that 70% ethanol extract produced total flavonoid levels of 8.6954% mgEK/mL and total phenolics of 15.4385% mgEAG/mL, higher than ethyl acetate extract with total flavonoid results of 3.418% mgEK/mL and total phenolics of 4.6052% mgEAG/mL. The results of antibacterial activity at concentrations of 12%, 14%, 16%, 70% ethanol extract were 10.5±0.70 mm; 12.1±0.28 mm; 14.3±0.57 mm, respectively, which had higher activity than ethyl acetate extract with results of 9.1±0.28 mm; 10.5±0.5 mm; 12.3±0.57 mm, the highest antibacterial activity at a concentration of 16%. Chemometric analysis using Principal Component Analysis (PCA) showed a strong positive correlation between phytochemical content and antibacterial activity. The highest antibacterial activity was found in the 70% ethanol extract at a concentration of 16%.